Mergers, acquisitions, and the pruning of managerial deadwood - Walsh, James P.; Ellwood, John William (Strategic Management Journal, 1991)
Abstract This research investigates the role that mergers and acquisitions may play in the disciplining of entrenched and inefficient managers. The relationship between a company's performance history and its subsequent top management turnover is assessed for a sample of target companies, their parents, and a control group of companies not involved in merger and acquisition activity. The results reveal that target company top management turnover is higher than ‘normal’ in the 2 years immediately following a merger or acquisition, but there is no relationship between previous target company performance and its subsequent top management turnover. Further analyses indicate that first‐year target company turnover rates are associated with a history of relatively poor parent company performance, while second‐year turnover rates are associated with a history of relatively good parent company performance.